(untitled) (Acta Entomológica Chilena, 2022)
Observations both at the laboratory and in the field prove that probably Rhagoletis tomatis has at least five to six generations per year. This species present a low pupal diapause. Females deposite their eggs gregariously in unripen fruits. After ovipositing the females dragg the ovipositor in circle near of puncture and probably deposit a pheromone that is atractive for other females.